2020
DOI: 10.1021/acs.analchem.0c01675
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Multiplex Detection of Single Nucleotide Polymorphisms Based on Short-Chain Hybridization Combined with Online Preconcentration of Capillary Electrophoresis

Abstract: Reliable multiple single nucleotide polymorphisms (SNPs) detection at low abundance is of great significance for disease diagnosis and biomedical research. Herein, we have developed a novel and simple method for multiple SNPs detection combining solid-phase capture by specific hybridization with online preconcentration of capillary gel electrophoresis-laser-induced fluorescence (CGE-LIF). The method presents an excellent performance due to its favorable traits: the solid-phase short-chain hybridization ensures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The limit of detection (3 σ/slope) was estimated as 0.36 fM. As shown in Table S2, this double-amplified detection system based on hairpin-empowered invasive reaction and CHA cascade reaction had a distinct advantage in detection sensitivity compared with detection strategies reported in many literature. , …”
Section: Resultsmentioning
confidence: 90%
“…The limit of detection (3 σ/slope) was estimated as 0.36 fM. As shown in Table S2, this double-amplified detection system based on hairpin-empowered invasive reaction and CHA cascade reaction had a distinct advantage in detection sensitivity compared with detection strategies reported in many literature. , …”
Section: Resultsmentioning
confidence: 90%
“…All of the PCR products were analyzed using CE with short-end injection, providing the advantages of high resolution and rapid separation. Zhou et al used solid-phase hybridization capture and CGE-LIF for the detection of multiple single nucleotide polymorphisms . FASI was used for the CGE online preconcentration, leading to a significant improvement in the detection sensitivity of the fluorescent probe by nearly 100-fold.…”
Section: Applicationsmentioning
confidence: 99%
“…Since a high electric field is applied to the sample zone, the electrophoretic migration of ionic analytes in the sample zone is faster than that in the BGE, resulting in the stacking of the analytes to a narrow zone at the sample/BGS boundary. In recent years, FASS has been employed to the CE analysis of organic mercury [12], nitrate [13], catecholamines [14], amino acids [14,15], single nucleotide polymorphisms (SNPs) [16], β2-agonist bronchodilator [17], endogenous metabolites [18], imatinib [19], fluoxetine [20], and adamantane analogs [21] as summarized in Table 1. As a typical application, Zhou et al reported CGE analyses of SNPs.…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%
“…As a typical application, Zhou et al reported CGE analyses of SNPs. By employing FASS, the detection sensitivity was improved to nearly 100-fold [16]. Wang et al combined FASS with on-line complexation using 3-mercapto-1-propanesulfonate for the speciation of organic mercury, which allowed the direct UV detection of three organic mercury complexes with the LOD of 11-16 ng/mL [12].…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%